Clinical concepts for treatment of the elbow in the adolescent overhead athlete - Ellenbecker, T. S.; Reinold, M.; Nelson, C. O. (Clinics in Sports Medicine, 2010)
Injuries to the adolescent elbow are common because of the repetitive overuse inherent in many overhead sport activities. The management of these patients is greatly facilitated through a greater understanding of the demands placed on the upper extremity kinetic chain during these overhead activities as well as a detailed examination and rehabilitation for the entire upper extremity kinetic chain. Particular emphasis on improving rotator cuff strength and muscular endurance, along with scapular stabilization, is a critical part of elbow rehabilitation in these patients. In addition, the use of a strategic and progressive interval sport return program is necessary to minimize reinjury and return the adolescent overhead athlete to full function.